RepRAP P3Steel spatial printer construction design - Cieślak, Robert; Suszyński, Marcin; Wiatrowski, Adrian (Technologia i Automatyzacja Montażu (Assembly Techniques and Technologies), 2020)
The introduction describes the purpose of the article, i.e. designing a REPRAP printer. The article includes an overview of additive manufacturing techniques. The next section discusses the definition of a self-replicating REPRAP printer. Then, the example of the method for extruding thermoplastic materials with the use of the FDM / FFF technique served to present the list of parts and the design of the REPRAP P3STEEL spatial printer. Tests were also carried out and the prints were compared with the Zoltrax M200 serial production printer. This is an Open Access article distributed under the terms of the Creative Commons Attribution License CC BY 4.0 (https://creativecommons.org/licenses/by/4.0/)